Limits of Nature and Advances of Technology: What Does Biomimetics Have to Offer to Aquatic Robots? - F. E. Fish (Applied Bionics and Biomechanics)
In recent years, the biomimetic approach has been utilized as a mechanism for technological advancement in the field of robotics. However, there has not been a full appreciation of the success and limitations of biomimetics. Similarities between natural and engineered systems are exhibited by convergences, which define environmental factors, which impinge upon design, and direct copying that produces innovation through integration of natural and artificial technologies. Limitations of this integration depend on the structural and mechanical differences of the two technologies and on the process by which each technology arises. The diversity of organisms that arose through evolutionary descent does not necessarily provide all possible solutions of optimal functions. However, in instances where organisms exhibit superior performance to engineered systems, features of the organism can be targeted for technology transfer. In this regard, cooperation between biologists and engineers is paramount.